CARA PENANAMAN SETEK BULUH BAMBU BETUNG, ANDONG, TEMEN, HITAM, DAN TALI - Sandra Arifin Aziz (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1997)
Experiments of the planting method of two nodes culm cuttings horizontally and one nodeculm vertically were carried out on Dendrocalamus asper, Gigantochloa pseudoarundinacea, and G. atter (Experiment I), and D. asper, G. atroviolacea, and G. opus (Experiment 2). FactorialRandomized Block Design were used, with the first factor: planting method of two nodes culmcuttings horizontally and one node culm cuttings vertically and bamboo species as the second factor. All combinations were replicated four times. Two nodes culm cuttings planted horizontally was better than one node culm cuttings planted vertically. Gigantochloa atter had the best growth percentage (60 %) and followed by G. pseudoarundinacea 56 %, D. asper 52 %, G. afroviolacea and G. apus < 10 %. G. apus could not be propagated vertically. Vertical planting with one node in the dry season is not advisable.